Effect of nanoemulsion carbonated hydroxyapatite-statin administration on Acp 5 and Runx-2 expression during orthodontic relapse in rats - Ananto Ali Alhasyimi; Niswati Fathmah Rosyida; Ika Dewi Ana (Journal of Oral Biology and Craniofacial Research)
Background: Retention is an essential element of orthodontic treatment. In the past two decades, numerous biological treatments have been developed to alleviate orthodontic relapse. Pharmacologic bone modulation is a viable approach to mitigate relapse. The aim of this investigation was to determine whether administering nanoemulsion carbonated hydroxyapatite-statin (CHA-statin) would increase Runx-2 expression and decrease Acp 5 expression in rats experiencing experimental orthodontic relapse. Materials & methods: Forty-eight rats (n = 48) were assigned to four groups: control, CHA, statin, and CHA-statin, with 12 rats in each group. A 30 g mesial traction was applied for 7 days via a closed-coil spring that connected the first maxillary molar to the maxillary incisor. To maintain the moved teeth, CHA, statin hydrogel, and nanoemulsion CHA-statin were administered intrasulcularly every 3 days for a period of 7 days. The removal of the devices facilitated the occurrence of relapse. The expression of Acp 5 and Runx-2 was evaluated using the immunohistochemistry method. The collected data were evaluated using analysis of variance and post hoc tests, with p < 0.05. Results: A significant reduction in Acp 5-positive cells in the CHA-statin group was observed on days 7 and 14 of relapse movement compared with the other groups (p < 0.05), whereas the average Runx-2 expressions in the CHA-statin groups were significantly higher than in the other groups on days 1, 7, and 14 during the relapse phase (p < 0.05). Conclusion: The nanoemulsion CHA-statin increased Runx-2 expression and decreased Acp 5 expression, thereby potentially preventing orthodontic relapse in rats.